2010
DOI: 10.1073/pnas.1008189107
|View full text |Cite
|
Sign up to set email alerts
|

High brain lactate is a hallmark of aging and caused by a shift in the lactate dehydrogenase A/B ratio

Abstract: At present, there are few means to track symptomatic stages of CNS aging. Thus, although metabolic changes are implicated in mtDNA mutation-driven aging, the manifestations remain unclear. Here, we used normally aging and prematurely aging mtDNA mutator mice to establish a molecular link between mitochondrial dysfunction and abnormal metabolism in the aging process. Using proton magnetic resonance spectroscopy and HPLC, we found that brain lactate levels were increased twofold in both normally and prematurely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
178
2
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 237 publications
(201 citation statements)
references
References 49 publications
20
178
2
1
Order By: Relevance
“…Under such conditions, it cannot be excluded that isoenzyme pattern may influence the time course of the lactate concentration. However, because the LDH activity is high, such transitions in net flux of the LDH reaction must be short-lived and are unlikely to explain the observations by Ross et al (1).…”
mentioning
confidence: 67%
See 1 more Smart Citation
“…Under such conditions, it cannot be excluded that isoenzyme pattern may influence the time course of the lactate concentration. However, because the LDH activity is high, such transitions in net flux of the LDH reaction must be short-lived and are unlikely to explain the observations by Ross et al (1).…”
mentioning
confidence: 67%
“…In their paper, Ross et al (1) suggested that high brain lactate is a marker of aging and that this lactate accumulation is explained by a shift in the lactate dehydrogenase (LDH) isoenzyme pattern also found to be associated with aging. Although the brain lactate increase with age is highly interesting, the suggested explanation may be problematic.…”
mentioning
confidence: 99%
“…Cooperation between brain and islet plays a critical role in the control of both energy and glucose homeostasis (52). Therefore, mitochondrial mutations/deletions in the central nervous system and other organs in mtDNA mutator mice might be crucial in the brain-centered regulation of glucose homeostasis via insulin-independent mechanisms (53).…”
Section: Aging Impairs In Vivo Glucose Homeostasismentioning
confidence: 99%
“…This technique, with early studies dating back to 1968, remains popular, with many considering it the "gold standard" for identifying mitochondrial diseases in patients 14,19,26,27 . It is now frequently used to investigate mtDNA mutation-driven aging and aging-related disorders 12,13,18,20,21,24 . The COX/SDH double-labeling method is often used in parallel with other techniques to identify specific mtDNA mutations and to further investigate the mitochondrial respiratory enzymes, such as oximetric measurements and spectrophotometric enzyme analysis 28,29 .…”
Section: Figure 1 Mitochondrial Respiratory Complexes I-vmentioning
confidence: 99%
“…Although other respiratory complexes could be investigated, Complexes IV and II are the most amenable to histochemical examination 8,9 . Complex II, or succinate dehydrogenase (SDH), is entirely encoded by nuclear DNA (Figure 1), and its activity is typically not affected by impaired mtDNA, although an increase might indicate mitochondrial biogenesis [10][11][12] . The impaired mtDNA observed in mitochondrial diseases, aging, and age-related diseases often leads to the presence of cells with low or absent COX activity 2,12-14 .…”
Section: Introductionmentioning
confidence: 99%